Future of Fishing for a Vulnerable Atoll: Trends in Catch and Catch-Per-Unit-Effort in Tokelau’s Domestic Marine Fisheries 1950–2016 - White, Rachel; Coghlan, Amy Rose; Coulter, Angie; Palomares, Maria Lourdes D.; Pauly, Daniel; Zeller, Dirk (Frontiers in Marine Science, 2018)
Tokelau is among the most vulnerable countries to climate change from both an environmental and economic perspective, whilst being highly dependent on marine resources for dietary nutrition. Industrial as well as small-scale fisheries are present in Tokelau’s waters, with Tokelau itself only participating in small-scale fisheries. Industrial fisheries consist exclusively of foreign distant-water tuna fleets. This study aims to reconstruct and investigate the trends in the domestic small-scale marine fisheries catches, fishing effort, and catch-per-unit-effort (CPUE) from 1950–2016. We used kWdays as our metric of fishing effort or fishing capacity, estimated using length, motorization and type of fishing vessels. Total fishing effort was approximately 11,900 kWdays in 1950 and increased rapidly after the 1980s with the introduction of larger motorized vessels. Despite evolving fishing effort, catches taken in subsistence fisheries have been relatively consistent at approximately 370 t∙year-1, resulting in a reduction of subsistence CPUE from 32.4 kg∙kWdays-1 in 1950 to 2.6 kg∙kWdays-1 in 2016. This trend is opposite to that of the artisanal fishery, where CPUE increased since the start of this fishery in 2003, from 1.7 kg∙kWdays-1 to 2.6 kg∙kWdays-1 in 2016. Tokelau’s domestic catch is greatly underreported, with reconstructed domestic catch since 2010 being nearly four times larger than the data reported by the Food and Agriculture Organization (FAO) of the United Nations on behalf of Tokelau. The abundance of reef fishes are predicted to decrease while the abundance of pelagic fishes is expected to increase within Tokelau’s waters due to climate change, likely further altering future fishing practices. The present CPUE analysis, combined with the forecasted effects of climate change, suggests that the domestic fisheries in Tokelau may be on an unsustainable path, highlighting food security concerns, despite the potential for growth in offshore fisheries.